ANALYSIS OF CONFLICT AND INTRINSIC ELEMENTS IN THE SHORT STORY ENTITLED “NARA DILEMA” BY ALYA KHALISAH IN STUDY OF LITERARY SOCIOLOGY - Aurin, Nasyah; Kabeakan, Nuraini; Nasution, Anggi Dwi Rosidi; Srimiati, Srimiati; Natasya, Rika (LUMBUNG AKSARA, 2023)
This study aims to investigate social conflict from the short story titled "Dilema Nara" by AlyaKhalisah. This approach is to understand the development and present the social reality about an unharmonious family. This study employs a qualitative descriptive method. The data collection technique in this study involves careful reading, noting, and case studies of conflicts present in the story. The instruments used in this study are note sheets and readings of the short story originating from a website. The steps taken in this study include identifying the problem, collecting data, presenting data, and making conclusions from the research results. The subject of this study is the short story titled "Dilema Nara" by Alya Khalisah.